2014
DOI: 10.12944/cwe.9.3.59
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Temperature on Rapeseed-Mustard Yield at Selected Locations in Chhattisgarh State

Abstract: Mustard is the second most important edible oilseed crop in India after groundnut and accounts for nearly 30 percent of the total oilseeds produced in the country. Weather parameters play major role in determining the crop growth, development and yield because weather strongly influences the physical expression of genetic potential of the crop. The present investigation aimed to find out relationship between maximum and minimum temperature during different stages of mustard crop and yield at three locations of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 0 publications
1
5
0
Order By: Relevance
“…Differences in demonstration yield of the same variety in different agro-ecological zones may be due to variation in soil health and other climatic conditions. These findings are in accordance with the finding of Khavse et al, (2014) who also found variation in yield of mustard at three different location of Chhattisgarh. Indian mustard var.…”
Section: Demonstration Yield Of Varietiessupporting
confidence: 93%
“…Differences in demonstration yield of the same variety in different agro-ecological zones may be due to variation in soil health and other climatic conditions. These findings are in accordance with the finding of Khavse et al, (2014) who also found variation in yield of mustard at three different location of Chhattisgarh. Indian mustard var.…”
Section: Demonstration Yield Of Varietiessupporting
confidence: 93%
“…These species belongs to the genus Brassica and family Brassicaceae and are called rapeseed-mustard in vernacularly language and are traditionally grown as the major groups of winter oilseed crops under irrigated and natural rainfall areas of India. India is one of the largest rapeseed mustard growing country in the world, occupying the first position in area and second position in production after China (Khavse et al, 2014). India accounts for 19.29 per cent and 11.13 per cent of the total acreage and production of rapeseed-mustard in the world, respectively (Anonymous, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, weather variability is an important abiotic stress, which is most harmful as it affects the growth and productivity of crops, resulting in a yield reduction. Generally, about 67% variation of any crop is governed by prevailing weather condition and 33% by other crop management factors (Khavse et al, 2014).…”
Section: Introductionmentioning
confidence: 99%